1990
DOI: 10.1210/endo-126-3-1343
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antibodies to Androgen-Dependent Secretory Proteins of the Mouse Dorsolateral Prostate*

Abstract: The mouse prostate is an attractive model for studying the relationship between epithelial-mesenchymal interactions and the mechanism of androgen action because of the volume of information on tissue interactions in the development of the prostate of this species and the existence of a mutant mouse lacking functional androgen receptors (Tfm mouse). In this paper the major proteins of the mouse dorsolateral prostate (DLP) have been described, and antibodies to these proteins have been characterized. The two mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 46 publications
2
38
0
Order By: Relevance
“…Androgens regulate normal prostate development and are required for prostate tumorigenesis. In both development and carcinogenesis, many of the androgenic effects on prostate epithelial cells are elicited via signaling through stromal AR (38)(39)(40). We confirmed that PCa growth in the bone is stimulated by androgenic effects on stromal cells and specifically by activation of Wnt signaling in preosteoblasts.…”
Section: Discussionsupporting
confidence: 64%
“…Androgens regulate normal prostate development and are required for prostate tumorigenesis. In both development and carcinogenesis, many of the androgenic effects on prostate epithelial cells are elicited via signaling through stromal AR (38)(39)(40). We confirmed that PCa growth in the bone is stimulated by androgenic effects on stromal cells and specifically by activation of Wnt signaling in preosteoblasts.…”
Section: Discussionsupporting
confidence: 64%
“…In fact, reliable histologic comparisons between lobes of the prostate can only be determined through meticulous anatomical dissections at the time of necropsy or through utilization of additional immunohistochemical staining for proteins unique to particular lobes of the prostate. 18 The prostate glands can be readily distinguished histologically from the seminal vesicles that characteristically display a more prominent ®bromuscular stroma with granular lumenal secretions ( Figure 1G) and from the ampullary glands that display a more prominent ®bro-muscular stroma with`Swiss cheese' like secretions ( Figure 1H). …”
Section: Grading Systemmentioning
confidence: 99%
“…An early study revealed that spermine-binding protein (SBP) and serine protease inhibitor Kazal type-3 (SPI-KT3) are abundant in the mouse VP (Mills et al 1987a(Mills et al , 1987b. Proteins secreted from the dorso-lateral prostate (DLP) and AP have not yet been identified, although Cunha's group developed a specific polyclonal antibody for major DLP protein(s) to be used as a differentiation marker (Donjacour et al 1990).…”
Section: Introductionmentioning
confidence: 99%